Quality Improvement of The Public Service of The Metal Contamination Testing Laboratory Using Lean Six Sigma Approach (Case Study) - Wulandari, Ratna Ayu; Prastawa, Heru; Budiawan, Wiwik (Formosa Journal of Science and Technology, 2024)
Testing laboratory public services play an important role in providing services to the public in various sectors. Currently, many laboratories only focus on the quality of testing but forget about the timeliness of testing services which affects customer satisfaction as a metric of public service performanceTherefore, to improve quality by achieving timeliness of testing services, this research uses a Lean and Six Sigma approach and risk management. Through the tools used such as Value Stream Mapping (VSM), Spaghetti Diagram, Fish-bone Diagram, PICK Chart in the Define, Measure, Analyze, Improve, and Control (DMAIC) phase of Lean Six Sigma, problems can be identified, analyzed and corrected for improvement. In the measure phase, the completion time for testing services was 17 working days so it did not meet the service time standard (timeliness) which is 16 working days. After the improve phase solution is implemented, the service turnaround time becomes 7 working days. Apart from achieving faster completion times for testing services, the improvement rate for eliminating NVAA was 99.5%, eliminating waiting and over-processing waste by 100%. In order for this achievement to remain controlled, risk statements regarding the timeliness of testing services are identified, analyzed, controlled and monitored. The results of improvement trials on samples, SPM testing services for Pb, Cd, Hg, As metal contamination in food reached 100%.